Disturbance in the Composition of the Intestinal Microflora in the Mechanisms of the Formation of Clinical Manifestations in Patients with Chronic Pancreatitis (Texas Journal of Medical Science, 2024)
To determine the role of a violation of the composition of the intestinal microflora in the formation of clinical manifestations and in structural changes of COD in patients with CP and to evaluate the effect of therapy aimed at restoring intestinal microbiosenosis on the course of the disease